Zoosporangia survival, dehiscence and zoospore formation, and motility in the green alga Rhizoclonium hieroglyphicum as affected by different factors - Gupta, S; Agrawal, S C (Folia microbiologica, 2004)
Urea at 200 ppm (probably serving as a nitrogen source), liquid Bold's basal medium at pH 7.5, temperature of about 22 degrees C and light intensity of about 40 micromol m(-2) s(-1) for 16 h a day induced rapid and/or abundant zoospores formation and zoosporangia dehiscence and favored zoospore liberation, speed and motility time period in the green alga Rhizoclonium hieroglyphicum. However, factors such as water stress (2 and 4 % agarized media, liquid media with 0.2-0.4 mol/L NaCl, 5-60 min blot-dryness of filaments), pH extremes of liquid media (at < or =6.5 and > or =9.5), temperature shock in liquid media (5 and 35 degrees C for > or =5 min), UV exposure (0.96-3.84 kJ/m2), lack of all nutrients from liquid medium (double distilled water), darkness, and presence of "heavy" metals (1-25 ppm Cu, Fe, Zn, Hg, Ni, Co) or organic substances (200-600 ppm captan or DDT, 800 and 1000 ppm 2,4-D, 50 and 400 ppm indole-3-acetic acid (3-IAA), 1000 and 2000 ppm urea, 100 and 200 ppm thiourea) in liquid media decreased and/or delayed at various levels either zoosporangia survival, zoospore formation or zoosporangia dehiscence and/or the rate of zoospore liberation from zoosporangia, zoospore speed and time period of motility in the media or totally inhibited all these processes. 3-IAA at 50 and 400 ppm induced zoosporangial papilla to grow into a tube-like projection of about 30-120 microm in length. Zoosporangial dehiscence rather than zoospore formation or zoosporangia survival, and zoospore motility period rather than zoospore speed are probably more sensitive to various adverse environmental factors. The rate of zoospores liberation from zoosporangium (possibly related directly to some extent on the zoospore number inside) is probably independent of zoospore speed in the medium.
Keywords: tma; Metals, Heavy; ultrafialové záření; pohyb; Chlorophyta; koncentrace vodíkových iontů; Darkness; těžké kovy; Spores; spory; Hydrogen-Ion Concentration; Temperature; Movement; kultivační média; Ultraviolet Rays; močovina; teplota; Urea; Culture Media